Improved quality of life and joint functions in patients with knee rheumatoid arthritis who underwent five portal arthroscopic synovectomy - Liu, Wen-Xin; Jiang, Yao; Hu, Qing-Xiang; You, Xie-Bo (PeerJ, 2018)
Objectives To evaluate the outcomes of patients with rheumatoid arthritis (RA) of the knee who underwent five portal arthroscopic synovectomy, with or without post-operative negative pressure drainage (NPD). Material and Methods A prospective clinical trial was performed. Patients with class I, II, and III RA of the knee were enrolled. They underwent five portal arthroscopic synovectomy. Post-operatively, they received either NPD (group A) or non-NPD (group B). Health assessment questionnaire (HAQ), disease activity score 28 (DAS 28), and Lysholm knee joint score were evaluated before the operations, and at six weeks, three months, and one year after the operations. Results A total of 36 patients were enrolled into the study, with 63.9% (23) female patients and mean age of 47.2 years old. All of the patients had clinical symptoms (joint swelling, pain, and dysfunction) for at least six months with poor responses to the traditional pharmaceutical therapy. There were 12, 16, and eight patients in class I, II, and III RA groups, respectively (six IA, six IB, eight IIA, eight IIB, four IIIA, and four IIIB). One year after the operation, patients had statistically significant improvements on HAQ, DAS 28, and Lysholm knee joint scores. More improvements were observed in patients with class I diseases. There were no statistically significant differences between group A and B. Conclusion Five portal arthroscopic synovectomy could increase the quality of life, decrease disease activities, and improve joint functions in patients with RA. More benefits were observed in patients with early disease developments. Patients in the NPD group did not show more improvements compared to the patients in the non-NPD group.
Keywords: Rheumatoid arthritis; Synovectomy; Negative pressure drainage; Arthroscopy